2016
DOI: 10.1007/s13201-015-0376-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zinc and lead on the physiological and biochemical properties of aquatic plant Lemna minor: its potential role in phytoremediation

Abstract: Plants have gained importance in situ bioremediation of heavy metals. In the present study, different concentrations of zinc (Zn 2? ) (0.5, 5, 10, 15, 20 mg/l) and lead (Pb 2? ) (1, 2, 4, 6, 8 mg/l) were used to evaluate metal tolerance level of Lemna minor. L.minor were exposed to metals for 4 days and tested for its dry to fresh weight ratio (DW/FW), photosynthetic pigments production and protein content. The oxidative damage was detected by measuring catalase activity. L.minor showed tolerance against Zn an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 32 publications
3
34
0
1
Order By: Relevance
“…Free proline can still maintain a higher concentration. These findings are correlated with work of Jayasri et al (2017). Their study of Pb stress on Lemna minor demonstrated that the decomposition of soluble protein accelerated under adverse circumstances and separated into various amino acid including free proline, etc., resulting in the rise of proline content.…”
Section: Discussionsupporting
confidence: 60%
“…Free proline can still maintain a higher concentration. These findings are correlated with work of Jayasri et al (2017). Their study of Pb stress on Lemna minor demonstrated that the decomposition of soluble protein accelerated under adverse circumstances and separated into various amino acid including free proline, etc., resulting in the rise of proline content.…”
Section: Discussionsupporting
confidence: 60%
“…Long et al [54] reported that shoot growth was significantly inhibited and shoot fresh weight decreased at Zn concentrations above 200 mg Lfor Chinese cabbage, pakchoi and celery. However, exposure of plant with zinc heavy metal in low concentration (10 mg/l) promotes Lemna minor growth, but it cause toxic effect at higher concentration (20 mg/l) [55]. When we evaluate the effects of different Zn concentrations on Zn accumulation in plant, maximum zinc accumulations were obtained in 10 and 30 mg/L Zn, respectively (18,788.82±217.14 mg/kg DW, 18,325.33±368.50 mg/kg DW) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These effects on growth are generally linked to metal toxicity which may arise due to the metal binding to sulfhydryl groups in proteins which may inhibit their activity or affect their structure. Metals may also cause the displacement of essential elements, which results in deficiency effects ( Jayasri and Suthindhiran, 2017 ).…”
Section: Discussionmentioning
confidence: 99%